Risk assessment of unlined oil pits leaking into groundwater in the Ecuadorian Amazon: A modified GIS-DRASTIC approach. (February 2022) - Durango-Cordero, J.; Saqalli, M.; Ferrant, S.; Bonilla, S.; Maurice, L.; Arellano, P.; Elger, A.
Abstract: This study evaluates the risk of groundwater contamination from unlined oil pits, in the Northern Ecuadorian Amazon (NEA). Applying spatial analysis, several maps were provided for its integration in land use planning, public health improvement and future site-specific investigations. Two main maps were produced: (1) a vulnerability indexed map using a modified DRASTIC model and (2) a hazard map based on the past (1995–1997) and present (2018) contamination using a weighted density equation. The hazard was derived from hydrocarbon contained in oil pits associated with a cost-distance analysis to obtain different maximum distance ranges (MDR), to model the surface of potentially impacted groundwater. The results indicate a total calculated hydrocarbons of 39 052 tons. A MDR from 500–10 000 km was retained to map aquifers at risk, the maximum surface potentially at risk covers 13% of the NEA, while 83% of the area represents low to medium-low vulnerability. This study led to several recommendations, such as the level of suitability of the available information, and what gaps should be filled to improve future research. A surface of 271–766.5 km in the 500-2000-m distance range should be prioritised for finer scale risk assessment. Highlights: Aquifer vulnerability was assessed in forested and agricultural lands in an oil exploited region. Sensitivity analysis utilising the DRASTIC model was robust. Risk was mapped using oil pit hazard, a modified DRASTIC index, and cost-distance analysis. Micro-slopes and the distance of transported pollutants from the source were the main factors influencing the surface at risk. Maximum impacted surface may reach 13% of the Northern Ecuadorian Amazon.